Bisphenol A Diglycidyl Ether (BADGE) and Bisphenol Analogs, but Not Bisphenol A (BPA), Activate the CatSper Ca2+ Channel in Human Sperm - Rehfeld, Anders; Andersson, A. M.; Skakkebæk, N. E. (Frontiers in Endocrinology, 2020)
Aim: Evidence suggests that bisphenol A diglycidyl ether (BADGE), bisphenol A (BPA), and BPA analogs can interfere with human male fertility. However, the effect directly on human sperm function is not known. The CatSper Ca2+ channel in human sperm controls important sperm functions and is necessary for normal male fertility. Environmental chemicals have been shown to activate CatSper and thereby affect Ca2+ signaling in human sperm. BPA has previously been investigated for effects on Ca2+ signaling human sperm, whereas the effects of other BPA analogs are currently unknown. The aim of this study is thus to characterize the effect of BADGE, BPA, and the eight analogs BPG, BPAF, BPC, BPB, BPBP, BPE, BPF, BPS on Ca2+ signaling and CatSper in human sperm. Methods: Direct effects of the bisphenols on Ca2+ signaling in human sperm cells were evaluated using a Ca2+ fluorimetric assay measuring changes in intracellular Ca2+. Effects via CatSper were assessed using the specific CatSper inhibitor RU1968. Effects on human sperm function was assessed using an image cytometry-based acrosome reaction assay and the modified Kremer’s sperm–mucus penetration assay. Results: At 10 µM the bisphenols BPG, BPAF, BPC, BADGE, BPB, and BPBP induced Ca2+ signals in human sperm cells, whereas BPE, BPF, BPS, and BPA had no effect. The efficacy of the chemicals at 10 µM is BPG>BPAF>BPC>BADGE>BPB>BPBP. Dose-response relations of BPG, BPAF, BPC, BADGE, BPB, and BPBP yielded EC50 values in the nM-µM range. The induced Ca2+ signals were almost completely abolished using the CatSper inhibitor RU1968, indicating an effect of the bisphenols on CatSper. All bisphenols, except BPBP, were found to dose-dependently inhibit progesterone-induced Ca2+ signals, with BPG and BPAF displaying inhibition even in low µM doses. BPG and BPAF were shown to affect human sperm function in a progesterone-like manner. Conclusion: Our results show that the bisphenols BPG, BPAF, BPC, BADGE, BPB, and BPBP can affect Ca2+ signaling in human sperm cells through activation of CatSper. This could potentially disrupt human sperm function by interfering with normal CatSper-signaling and thus be a contributing factor in human infertility, either alone or in mixtures with other chemicals.